1985
DOI: 10.7863/jum.1985.4.11.595
|View full text |Cite
|
Sign up to set email alerts
|

In utero sonographic detection of hand and foot deformities.

Abstract: The in utero sonographic detection of some of the more subtle anomalies of the hand and foot is now possible with the improved resolution of the newer ultrasound equipment. Nine case reports of fetal hand and/or foot deformities are presented, with 12 total lesions. The deformities include clinodactyly, symbrachydactyly, talipomanus, talipes, and "rockerbottom" foot. The sonographic appearance of each of these is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 0 publications
3
16
1
Order By: Relevance
“…The carpal bones are normally not noticeable in the x-ray at this age. It is known that ossification of the phalanges takes place antenatally, while the carpal bones ossify postnatally 6. Limb anomalies can usually be diagnosed by antenatal ultrasound scan; nevertheless, we missed the diagnosis antenatally, mainly due to lack of suspicion for such potential deformities with the use of finasteride in pregnancy.…”
Section: To the Editormentioning
confidence: 96%
“…The carpal bones are normally not noticeable in the x-ray at this age. It is known that ossification of the phalanges takes place antenatally, while the carpal bones ossify postnatally 6. Limb anomalies can usually be diagnosed by antenatal ultrasound scan; nevertheless, we missed the diagnosis antenatally, mainly due to lack of suspicion for such potential deformities with the use of finasteride in pregnancy.…”
Section: To the Editormentioning
confidence: 96%
“…Numerous studies have reported on the feasibility of prenatal diagnosis of trisomy 18 by ultrasonography [6][7][8][9][10][11]. The most common findings include: strawberryshaped head, ventriculomegaly, posterior fossa cyst, facial cleft micrognathia, nuchal edema, diaphragmatic hernia, heart defects, exomphalos, esophageal atresia, renal defects, intrauterine growth retardation and abnormalities of the extremities [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the hands the most common findings are overlapping fingers, persistent abnormal position of the fetal fingers, a clenched wrist, and upper limb reduction such as aplasia or hypoplasia of the radius and thumb [1,6,7,13,14]. Abnormal position of the fetal fingers or clenched fist is the most common finding in trisomy 18, found in 90% of the cases and as Shields et al reported in their series of 35 fetuses with trisomy 18 this may be the only finding in some cases [8].…”
Section: Discussionmentioning
confidence: 99%
“…a convex plantar surface is observed, together with posterior bulging of the calcaneus (Fig. 9)(9). Sonographically, this convexity plus protrusion behind the posterior calf line of the heel can be observed.…”
Section: Anomalies Of the Footmentioning
confidence: 99%